Guía para la contabilidad experimental de la cobertura vegetal del sistema agro-silvo pastoril del Campus CEASA periodo 2020. - Zhagñay Naspud, Rosa Virginia (2020)
The main objective of this project was the compilation of a guide for experimental accounting of vegetal cover of agro-silvo pastoral system of CEASA Campus. Considering that ecosystem accounting assesses the services provided by plant cover, thematic accounts such as carbon, water, and biodiversity accounting that have been established, also carrying out an inventory of existing species in the project area through the field research. Where only seven tree plants have been identified where it will be possible to carry out carbon accounting because they have considerable Dap. In other hand, two found bushy plants will not be used for carbon accounting since they have a smaller amount of litter and their diameter. Consequently, the development of the guide has focused on environmental accounting assets such as plantations, livestock and forestry which are based on the Environmental-Economic Accounting System for Agriculture, forestry and fishing (MAR AFF) (2020) where proposes that after an exhaustive field work an assessment will be given to the vegetation cover. All of this aims to comply with the provisions of Ecuador Republic Constitution Art, 14 of Sumak Kawsay (2015), which reiterates that living in a healthy and ecologically balanced environment will stop the degradation of soils (p.14).